Filmische Poetiken der Schuld. Die audiovisuelle Anklage der Sinne als Modalität des Gemeinschaftsempfindens - Grotkopp, Matthias (Cinepoetics. Poetologien audiovisueller Bilder, 2017)
How do cinematic images generate and transform a community's affectively grounded sense of values? Using the feeling of guilt as an example, this study shows how modulation of moral sentiments can be described as the calculus of audiovisual staging techniques. This calculus is analyzed as a cultural practice that helps establish the conditions for political community and shapes its historicity.